EXCHANGE RATE, GOLD PRICE, AND STOCK PRICE CORRELATION IN ASEAN-5: EVIDENCE FROM COVID-19 ERA - Vicho Dwindra Arisandhi; Robiyanto Robiyanto (Jurnal Manajemen dan Kewirausahaan, 2022)
ASEAN-5 (Indonesia, Singapore, Malaysia, Philippines, and Thailand) were the pillars of economies in the Southeast Asia. This study aimed to examine the dynamic correlation of exchange rate and gold price on stock price in ASEAN-5 countries during COVID-19 pandemic. This study used Asymmetric DCC-GARCH model and employed daily data from March 2020 to August 2021. For all cases, the findings showed the degree of correlations were similar to each other. Furthermore, the result revealed that exchange rate and gold price had weak correlations on stock price. During the pandemic, negative correlation confirmed the exchange rate was a better alternative asset than gold which was positively correlated with stock prices. The ASEAN-5 market participants should hereby evaluated their investment risk and strategy.